MANAJEMEN KEMITRAAN SEKOLAH-KELUARGA (MKSK) BERBASIS MODEL EPSTEIN: PERAN KRITISNYA DALAM MENDORONG PERKEMBANGAN KEMANDIRIAN HOLISTIK ANAK USIA DINI - Hartinah; Dadan Suryana (STKIP Subang, 2025)
The development of early childhood (ECD) independence is an important foundation for future learning success and social adjustment. However, this development requires a consistent stimulating environment between home and school. This study aims to empirically analyze (quantitative data simulation) how much significant influence Management of School-Family Partnership (MKSK) has on Early Childhood Independence. MKSK refers to a structured collaboration between schools and parents, which in this study is measured using Joyce L. Epstein's Six Types of Engagement Model framework. The method used was correlational quantitative research with a simulation subject of N=172 parents of PAUD/TK students. MKSK and Independence data were measured using validated questionnaire instruments, then analyzed using Multiple Linear Regression analysis. The main results showed that MKSK has a positive and significant effect on Early Childhood Independence, with a regression coefficient of B=0.756 (p<0.001). MKSK was found to account for 45.2% of the variation in children's Independence scores. This finding provides strong evidence that planned partnership management - particularly through two-way communication (Type 2) and home learning support (Type 4) - is an essential strategy for ECD units to create an environment conducive to the optimal development of children's independence.